PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR IPS - Siti Zulaihah; Aniek Rahmaniah (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The low understanding of students in social science subject matter due to the use of learning models that are not suitable for students, if this is left alone, it will affect the low interest in learning students so that the learning outcomes are also less satisfactory. The purpose of this study is to determine: (1) planning a direct instruction learning model on social science subjects in MTs Muhammadiyah 09 Weru, Paciran, Lamongan; (2) the application of direct instruction learning models to improve student interest and learning outcomes; (3) inhibiting factors in increasing student interest and learning outcomes using a direct instruction learning model. The method used is descriptive qualitative. The data collection technique uses observation, interview and documentation techniques. The results showed that the application of the direct instruction learning model was able to increase students' interest and learning outcomes in social science subjects. The increase in students' interest in learning is in accordance with the indicators of interest in learning, namely the feeling of liking; active participation in activities; paying more attention without anyone telling, as well as learning outcomes as evidenced by an increase in competency test scores. The increase in interest and learning outcomes also does not escape the inhibiting factors such as the less strategic state of the classroom, as well as interference from friends outside the classroom. Abstrak Rendahnya pemahaman siswa pada materi pelajaran ilmu pengetahuan sosial karena penggunaan model pembelajaran yang kurang sesuai dengan siswa, jika hal tersebut dibiarkan saja maka akan berpengaruh pada rendahnya minat belajar siswa sehingga hasil belajarnya juga kurang memuaskan. Tujuan penelitian ini adalah untuk mengetahui: (1) perencanaan model pembelajaran direct instruction pada mata pelajaran ilmu pengetahuan sosial di MTs Muhammadiyah 09 Weru, Paciran, Lamongan; (2) penerapan model pembelajaran direct instruction untuk meningkatkan minat dan hasil belajar siswa; (3) faktor penghambat dalam meningkatkan minat dan hasil belajar siswa menggunakan model pembelajaran direct instruction. Metode yang digunakan yaitu kualitatif deskriptif. Adapun teknik pengumpulan datanya menggunakan teknik observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran direct instruction mampu meningkatkan minat dan hasil belajar siswa dalam mata pelajaran ilmu pengetahuan sosial. Peningkatan minat belajar siswa sudah sesuai dengan indikator dari minat belajar yaitu perasaan lebih menyukai; partisipasi aktif dalam kegiatan; memberi perhatian lebih tanpa ada yang menyuruh, begitupun dengan hasil belajar yang dibuktikan dengan peningkatan nilai uji kompetensi. Dalam peningkatan minat dan hasil belajar juga tak luput dari faktor penghambatnya seperti keadaan ruang kelas yang kurang strategis, serta gangguan dari teman luar kelas.